2004
DOI: 10.1177/112972980400500109
|View full text |Cite
|
Sign up to set email alerts
|

Early Rupture of Subclavian Vein Catheter: A Case Report and Literature Review

Abstract: Prolonged venous access devices (PVADs) have become indispensable in antiblastic protocols for the treatment of cancer patients, in anti-infection protocols for acquired immunodeficiency syndrome (AIDS) patients and in the management of chronic malabsorption syndromes. Using these catheters carries the risk of several complications, and some are potentially lethal, for example, cardiac embolization of catheter fragments. Rupture is a complication almost exclusive to catheters positioned percutaneously: after u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…10 Sarzo and colleagues suggested that the catheter is enveloped by a fibrin sleeve right after the implantation and caused an antireflux valve mechanism, preventing blood collection or treatment infusion. 12 The catheter wall is weakened by repeated attempts to clear the catheter by applying an excessive force on the syringe plunger, and this could explain the cases of catheters fragmenting shortly after their implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Sarzo and colleagues suggested that the catheter is enveloped by a fibrin sleeve right after the implantation and caused an antireflux valve mechanism, preventing blood collection or treatment infusion. 12 The catheter wall is weakened by repeated attempts to clear the catheter by applying an excessive force on the syringe plunger, and this could explain the cases of catheters fragmenting shortly after their implantation.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Fragmentation may have more than one cause. 11,12 Aitken and Minton defined “pinch-off sign” as friction of a catheter positioned too medially between the clavicle and the first rib. 11 The catheter narrows owing to the mechanical compression in the costoclavicular passage.…”
Section: Discussionmentioning
confidence: 99%